2020
DOI: 10.1002/alr.22743
|View full text |Cite
|
Sign up to set email alerts
|

Olfactory cleft mucus proteome in chronic rhinosinusitis: a case‐control pilot study

Abstract: Background Mechanisms of smell loss in chronic rhinosinusitis CRS are still unclear and likely multifactorial Little attention has been given to olfactory cle OC mucus proteins involved in odorant binding and metabolizing enzymes and their potential role in smell loss Methods Mucus from the OC was sampled from patients with CRS n = and controls n = Liquid chromatography and mass spectrometry were performed followed by data processing so that protein groups could be identified quantified and compared Hierarchic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 35 publications
(95 reference statements)
0
7
0
Order By: Relevance
“…1 Understanding the etiopathology of CRSsNP as well as developing an effective treatment remains challenging, although recent advantages have been made. [25][26][27][28][29][30] Current therapies are based on patient phenotype, and subtypes based on significant underlying immunologic differences are not considered. 31,32 Accordingly, these patients' clinical responses on medical therapy can be highly variable [33][34][35] and relapse surgery is often required.…”
Section: Discussionmentioning
confidence: 99%
“…1 Understanding the etiopathology of CRSsNP as well as developing an effective treatment remains challenging, although recent advantages have been made. [25][26][27][28][29][30] Current therapies are based on patient phenotype, and subtypes based on significant underlying immunologic differences are not considered. 31,32 Accordingly, these patients' clinical responses on medical therapy can be highly variable [33][34][35] and relapse surgery is often required.…”
Section: Discussionmentioning
confidence: 99%
“…Olfactory cleft mucosal sampling under nasal endoscopy was performed in the clinic and a sterile filter membrane (Leukosorb, Pall Corporation) was placed into the OC bilaterally under direct visualization, as previously published. [19][20][21] After 2 min, the membrane was removed, placed directly on ice, and centrifuged for 10 min at 13,000 rpm in 4 • C. The mucus from both sides were combined, 1× protease inhibitor (Halt, Thermo Fisher) added, and stored at −20 • C prior to assay conduction.…”
Section: Olfactory Cleft Mucosal Samplingmentioning
confidence: 99%
“…studied OC mucus proteins from CRSwNP, CRSsNP, and controls. They found that Lipocalin-1 and Lipocalin-15 which are thought to play a role in odorant binding, and glutathione S-transferases (GSTs), alcohol dehydrogenases, and other oxidizing enzymes, which are thought to play a role in odorant metabolism were downregulated in CRSwNP ( 28 ). Their findings suggest OC mucus dysregulation may indeed be associated with olfactory dysfunction in CRS patients.…”
Section: Mass Spectrometry-based Proteomics Of Chronic Rhinosinusitis...mentioning
confidence: 99%